Effect of SARS-CoV-2 infection on anti-HLA antibodies and de novo donor specific antibodies incidence in lung transplant recipients - Zajacova, Andrea; Dvorackova, Eliska; Casas-Mendez, Luis Fernando; Vychytilova, Katerina; Rakita, Dmitry; Valentova-Bartakova, Lucie; Svorcova, Monika; Slavcev, Antonij; Fila, Libor; Lischke, Robert; Havlin, Jan (Transplant immunology, 2023)
PURPOSE: There are no clear guidelines on how to handle immunosuppression in lung transplant recipients (LTRs) infected by SARS-CoV-2. Antimetabolite reduction with corticosteroid escalation is the most frequent strategy. The aim of this study was to determine the effect of this therapeutic approach on the incidence of de novo donor specific-antibodies (dnDSA). METHODS: We retrospectively analysed a cohort of 27 LTRs diagnosed with SARS-CoV-2 infection between September 2020 and April 2021 with available anti-HLA antibodies screening before and after infection. Managed as per the centre's SARS-CoV-2 protocol, the treatment modalities included specific virostatic treatment, convalescent plasma administration, reduction or discontinuation of mycophenolate and transient corticosteroid escalation initiated in the second week post-infection. RESULTS: All 27 patients received virostatics: 15 (55.6%) remdesivir and 12 (44.4%) favipiravir. In addition, 18 patients (66.7%) underwent convalescent plasma therapy. Of the 27 patients, 25 (92.6%) received mycophenolate as a part of their maintenance immunosuppressive regimen, which was temporarily reduced in 10 (37%) and discontinued in 15 LTRs (55.6%), the median resumption times for mycophenolate daily doses of at least 1000 mg being 13 days (IQR 11.0-63.5) and 59 days (IQR 26.0-130.0), respectively. Corticosteroids were escalated in 25 patients (92.6%), of whom 9 (33.3%) received IV methylprednisolone (median 80 mg/day; IQR 80-187.5) and 16 (59.3%) had oral prednisone adjusted (median 20 mg/day; IQR 16.3-38.8). The median time to revert to the corticosteroid dosage of ≤20 mg/day was 42 days (IQR 36.0-87.0). Notably, no dnDSA were detected in any LTR between 1 and 9 months from the onset of the SARS-CoV-2 infection. CONCLUSION: Our findings suggest that antimetabolite cessation with a transient corticosteroid escalation is a safe therapeutic strategy regarding anti-HLA dynamics in SARS-CoV-2 infected LTRs.
Keywords: Humans; hormony kůry nadledvin; Mycophenolate; antilymfocytární sérum; Lung; Antilymphocyte Serum; lidé; plíce; imunosupresiva; Lung transplantation; COVID-19; Immunosuppressive Agents; sérologická léčba covidu-19; Retrospective Studies; protilátky; Donor specific antibodies; antimetabolity; incidence; Incidence; COVID-19 Serotherapy; Antibodies; SARS-CoV-2 infection; příjemce transplantátu; Transplant Recipients; retrospektivní studie; Antimetabolites; Adrenal Cortex Hormones; SARS-CoV-2